Interfacial layer formation during the growth of Gd2O3 on Si(001) and its thermal stability. (19th October 2021) - Gribisch, Philipp; Fissel, Andreas
Abstract: The thermal stability of monoclinic Gd2 O3 grown on Si(001) as well as changes of the interfacial layer formed during the growth are investigated during rapid thermal annealing in nitrogen atmosphere between 600 °C and 1000 °C using x-ray diffraction and transmission electron microscopy (TEM). The monoclinic Gd2 O3 layer was grown at 400 °C and oxygen partial pressure of 5 × 10 −7 mbar. The Gd2 O3 layers exhibit first an initial strain release during annealing at 800 °C and subsequent induced thermal strain after annealing at 1000 °C. Thereby, the monoclinic structure remained unchanged. The interfacial layer formation during the growth is discussed in the framework of different physical effects, such as the presence of a nucleation barrier or the presence of a partially oxidized surface. The interfacial layer thickness increases with increasing annealing temperature, which can be attributed to the presence of oxygen and the high diffusivity during the annealing. The TEM investigations show a change in the layer contrast, which indicates a change in the interfacial layer composition. This could be due to the accumulation of oxygen and a subsequent release at higher temperatures.